The Protagonists (antagonists and assistants) and empowered”: competitive narratives in the school environment - Estefogo, Francisco (The ESPecialist, 2022)
This article aims, from a philosophical perspective, to reflect on the competitive and deleterious narratives in relation to the use of the terms protagonism and empowerment which normally echo in the school environment. It is based, in particular, on the philosophical conceptions of Aristotle (1997, 1998, 2011), with regard to the common well-being of the collectivity, as well as on the assumptions of Foucault (2010a, 2008, 1999, 1979), when it comes to talking about the discourses that structure the Law and the Truth. In the end, proposals will be made on the construction of agencies in favor of the power of the collectivity, with a view to community contentment, as well as the softening of the forces of power to prospect a society with more equitable and democratic opportunities for all citizens.